Growth Mindset and College Students’ Learning Engagement During the COVID-19 Pandemic: A Serial Mediation Model - Zhao, Hui; Xiong, Jianping; Zhang, Zhen; Qi, Chunhui (Frontiers in Psychology, 2021)
Against the scourge of the COVID-19 pandemic, college students’ learning engagement has become a key issue in universities and society. Guided by the theories of existential positive psychology and social perception, we explored the positive effect of a growth mindset on learning engagement during the COVID-19 pandemic. A total of 1,040 college students from universities in Henan Province of China effectively completed online questionnaires. The results showed that growth mindset was positively related to learning engagement and negatively associated with perceived COVID-19 event strength and perceived stress; perceived COVID-19 event strength was positively related to perceived stress, while perceived COVID-19 event strength and perceived stress were negatively associated with learning engagement. Growth mindset affected learning engagement through three indirect paths: the mediating role of perceived COVID-19 event strength, the mediating role of perceived stress, and the serial mediating role of both perceived COVID-19 event strength and perceived stress. The results indicated that the growth mindset could contribute to college students’ learning engagement through the roles of perceived COVID-19 event strength and perceived stress during the COVID-19 pandemic. This study advances the understanding of the mechanism underlying the relationship between growth mindset and college students’ learning engagement during the COVID-19 pandemic. Furthermore, the findings of the study have important implications for promoting college students’ learning engagement during the pandemic.